A Sodium Manganese Oxide Cathode by Facile Reduction for Sodium Batteries. Issue 6 (1st April 2014) - Song, Jinju; Gim, Jihyeon; Kim, Sungjin; Kang, Jungwon; Mathew, Vinod; Ahn, Docheon; Kim, Jaekook
Abstract A nonstoichiometric sodium manganese oxide (NaxMnO2+δ) cathode useful for sodium batteries was synthesized by an ambient‐temperature strategy that involved facile reduction of aqueous sodium permanganate in sodium iodide and subsequent heat treatment at 600 °C. Combined powder X‐ray diffraction and synchrotron X‐ray diffraction analyses confirmed the annealed sample to belong to a NaxMnO2 phase with a P2‐hexagonal structure. The ICP‐AES results confirmed the stoichiometry of the sample to be Na0.53MnO2+δ. Electron microscopy studies revealed the particle size of the electrode to be in the range of a few hundred nanometers. The Na0.53MnO2+δ cathode delivered an average discharge capacity of 170 mA h g−1 with a stable plateau at 2.1 V for the initial 25 cycles versus sodium. Ex situ XANES studies confirmed the reversible intercalation of sodium into Na0.53MnO2+δ and suggested the accommodation of over‐stoichiometric Mn4+ ions to contribute towards the performance of the electrode.